Penerapan Program Kampung Hijau Sebagai Wujud Lingkungan Yang Asri dan Bersih - Siti Vivi Junpahira; Azzahro, Amelia Risma (Abimanyu : Jornal of Community Engagement, 2023)
The mindset of the community towards the importance of protecting the environment and waste management needs to be addressed because it is stated in the regulations regarding the importance of protecting the environment. Five implementations of green villages arranged systematically. The implementation of the Green Village Program is divided into two with a Green Community approach to increase active participation from the community. Besides being useful for making the environment cleaner and more beautiful, the green village program activities also increase the community's passive income. The green village program that has been completed with the community is expected to continue even though the students have been withdrawn, even though these activities are carried out independently or together with a collective system with the RT. The success and success of the green village program is not far from the intervention and involvement of the community and local officials. Keywords: waste, program, green village, community, environment.